Repurposing of Bryophyllum pinnatum for dysmenorrhea treatment: a systematic scoping review and case series - Zurfluh, Leonie; Spinelli, Marialuigia Giovannini; Betschart, Cornelia; Simões-Wüst, Ana Paula (Frontiers in Pharmacology, 2023)
Dysmenorrhea affects women throughout their reproductive years but there has been a lack of effective and well-tolerated treatment options. Pain symptoms mainly result from inflammatory processes and increased contractile activity in the myometrium. The reported use of Bryophyllum pinnatum preparations against inflammation and pain in ethnomedicine as well as current pharmacological data on their inhibition of myometrial contractility led us to hypothesize that this medicinal plant might be a new treatment option for dysmenorrhea. In the first part of the present work, clinical, in vivo, and in vitro studies on the anti-nociceptive and anti-inflammatory, as well as on myometrium relaxing properties of B. pinnatum are reviewed. In the second part, cases of five women with dysmenorrhea who were tentatively treated with a B. pinnatum product are described. The review revealed thirty-three experimental in vivo and in vitro studies, but no clinical study, reporting anti-nociceptive and anti-inflammatory effects of B. pinnatum extracts and compounds in a wide range of conditions. Moreover, sixteen publications on smooth muscle contractility revealed relaxing effects. The latter consisted of clinical evidence, as well as of in vivo and in vitro data. The evidence reviewed therefore provided a rational basis for the use of B. pinnatum in the treatment of dysmenorrhea. We subsequently set out to tentatively treat patients with a well-tolerated B. pinnatum product that is registered (without indication) and commonly used in obstetrics and gynecology in Switzerland. All five treated patients reported a reduction in pain symptoms and 4 out of 5 indicated a reduced intake of painkillers during menstruation. Taken together, the reviewed information on the pharmacological properties and clinical evidence of B. pinnatum extracts and compounds as well as the outcomes of all five patients in the case series support our hypothesis in favor of B. pinnatum as a new, well-tolerated therapeutic approach for dysmenorrhea. Prospective clinical studies are urgently needed.